Experimental results of vector control for an asynchronous machine - Zineb Mekrini; Seddik Bri; Jamal Bouchnaif; Badre Bossoufi (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
The aim of this article is contributeto the advanced vector control strategy of asynchronous machines. Analyzes of experimental of indirect field-oriented control are presented. In this context, we propose vector control algorithms to provide solutions to the disadvantages of field-oriented control FOC.The results obtained from various methods of determining the parameters for asynchronous machine are compared. We calculate the various parameters and then we present the technical characteristics of each element of the asynchronous machine; finally, we implement the vector control used asbasis of comparison between the simulation under Matlab/Simulink software and experiments. The simulation and experimental tests show that the proposed controller is suitable for medium and high-performance applications.